Analyzing and Combating Drinking Liquor in “Bartender” of Hemin Mukeriany with Two Poems of Drinking Liquor of Manuchari Damghani - Hemn Karim M. Salih; Mariwan Hussein Farhan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Wine and drinking as important themes have always had clear reflections in the world of literature. Poets demonstrate their excessive zeal to the assemblage of wine and drinking. This type of literature originates from Persian literature with Rudaki and keeps being one of the underlying themes until reaches the top with Damghani. In Kurdish literature, Wine-purely secular meaning – as a dominant and pivotal theme starts with Hemn Mukryani. For thus reason Hemn is appointed among other Kurdish poets for this study. This article addresses this question, how wine and drinking reflect in both Poet’s work. In a descriptive way, this article analyses a poem of Hemn and two poems of Damghni as materials of the study. Mutual aspects of wine and drinking can be noticed in their poems. Like Damghani, Hemn uses wine to take pleasure and as sort of escapism from difficulties of life.